Trinidad and Tobago. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Trinidad and Tobago during 2011 are identified, with respect to the needs and interests of the country, strengthening topics such as training, technical assistance, greenhouse, agrotourism, food processing, agribusiness, food production, risk management, agricultural journalism, inclusion of women and the value chains of mango, cocoa, coffee, herbs and spices.